Legal Protection for Couriers Against Consumers Who Are Not Responsible for Cod Packages (Cash on Delivery) - Fita Rahmawati (Proceedings Series on Social Sciences & Humanities, 2023)
Electronic transactions or e-commerce there is an online mall or marketplace, which is a platform that can directly become an intermediary for all transactions between sellers and buyers. One of the payment methods known to the public is the COD (Cash On Delivery) system, where payment is made when the courier delivers the ordered goods to the customer's home. This causes problems that are often experienced by couriers delivering ordered goods. Often there are several customers who commit irresponsible acts by not being willing to pay for the COD package that has been ordered. Actions such as those mentioned certainly violate the agreement between buyers and sellers who use the Cash On Delivery method, where payment must be made when the courier has delivered the order to the buyer's address. This study aims to determine the legal protection of couriers and liability for COD (Cash On Delivery) packages. This research is made with a normative juridical method through a legal approach supported by primary, secondary and tertiary legal materials. The result of this research is the legal protection of courier rights for consumers who are not responsible for the COD package they bought.